2021
DOI: 10.1080/13607863.2020.1870207
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Cognitive Emotion Regulation Questionnaire (CERQ) in Spanish older adults

Abstract: The Cognitive Emotion Regulation Questionnaire (CERQ) assesses nine cognitive strategies used to cope with negative events. The aim of this study was to generate validity evidences of this instrument in an older Spanish population. The Spanish version of the CERQ (CERQ-S) and self-report scales, measuring psychological well-being, depression and resilience, were administered to 305 older adults aged 65-90 (70.0 ± 4.7) residents in the Autonomous Community of Madrid, Spain. 150 participants completed the 6-mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
31
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 58 publications
6
31
0
5
Order By: Relevance
“…Abbreviations: BPD, borderline personality disorder; CERQ, Cognitive Emotion Regulation Questionnaire; DERS, Difficulties in Emotion Regulation; HARS, Hamilton Anxiety Rating Scale; HCs, healthy controls; HDRS, Hamilton Depression Rating Scale; MDD, major depressive disorder. a Although no across-group differences were observed in these variables, in clinical groups, these values significantly differed (one-sample t-tests) from those obtained in a population of nondepressed older adults[18]: CERQ reappraisal (lower values in clinical groups), HCs: p = 0.882 (n.s. ), BPD: p = 0.098 (trend-level), MDD: p = 0.017; CERQ rumination (higher values in all groups), HCs: p = 0.019, BPD: p < 0.0005, MDD: p = 0.001.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Abbreviations: BPD, borderline personality disorder; CERQ, Cognitive Emotion Regulation Questionnaire; DERS, Difficulties in Emotion Regulation; HARS, Hamilton Anxiety Rating Scale; HCs, healthy controls; HDRS, Hamilton Depression Rating Scale; MDD, major depressive disorder. a Although no across-group differences were observed in these variables, in clinical groups, these values significantly differed (one-sample t-tests) from those obtained in a population of nondepressed older adults[18]: CERQ reappraisal (lower values in clinical groups), HCs: p = 0.882 (n.s. ), BPD: p = 0.098 (trend-level), MDD: p = 0.017; CERQ rumination (higher values in all groups), HCs: p = 0.019, BPD: p < 0.0005, MDD: p = 0.001.…”
mentioning
confidence: 86%
“…All participants completed the validated Spanish versions of the Cognitive Emotion Regulation Questionnaire (CERQ) and the Difficulties in Emotion Regulation Scale (DERS) to evaluate emotion dysregulation. Likewise, all subjects also completed the Hamilton Depression Rating Scale and Hamilton Anxiety Rating Scale to assess severity of depression and anxiety symptoms, respectively (18)(19)(20)(21)(22)(23)(24).…”
Section: Psychometric Assessmentmentioning
confidence: 99%
“…Moreover, the higher score means that the person uses the strategy more frequently in response to a negative event [35]. CERQ has been validated for different languages and populations, for instance: adolescents aged 14-18 [36] and older aged adults 65-90 [37] in Spanish, university students in Brazilian [38], and adults with recurrent depression [39].…”
Section: Adaptive / Maladaptive Cognitive Emotion Regulation Strategies (Cers)mentioning
confidence: 99%
“…To evaluate these nine strategies, Garnefski et al [ 19 ] proposed the Cognitive Emotion Regulation Questionnaire (CERQ), which is the first and only emotion regulation assessment instrument that separates cognitive regulation strategies from behavioural strategies [ 33 ]. It is one of the most widely used instruments for the assessment of emotion regulation and has shown its usefulness in different fields, such as clinical [ 34 ] or educational [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, McKinnon et al [ 45 ] reported that a five-factor model provided the best fit in an adult clinical population. In relation to the Spanish population, Carvajal et al [ 33 ] found that reducing the scale to 27 items improved model fit. Holgado-Tello et al [ 46 ] supported this 27-item version of the CERQ.…”
Section: Introductionmentioning
confidence: 99%